2022
DOI: 10.3233/jpd-223157
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Equivalent Aerobic Exercise Parameters Between Early-Stage Parkinson’s Disease and Pink1 Knockout Rats

Abstract: Background: Rodent Parkinson’s disease (PD) models are valuable to interrogate neurobiological mechanisms of exercise that mitigate motor impairment. Translating these mechanisms to human PD must account for physical capabilities of the patient. Objective: To establish cardiovascular parameters as a common metric for cross-species translation of aerobic exercise impact. Method: We evaluated aerobic exercise impact on heart rate (HR) in 21 early-stage PD subjects (Hoehn Yahr ≤1.5) exercising in non-contact boxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 90 publications
5
11
0
Order By: Relevance
“…This is the first study, to our knowledge, to explore the PINK1 -/- rat’s capability to complete a food incentivized maze, during the premotor phase. In line with the findings of this study, prior cohorts of PINK1 -/- rats in our laboratory have consistently exhibited hyperkinetic behavior before the age of 6 months [8]. Notably, these outcomes contrast with reports from other studies, where the timing of initial motor deficits and the extent of dopamine (DA) loss in this model range widely, with some indicating no deficits and others observing deficits emerging between 4 to 8 months [7-9, 31].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This is the first study, to our knowledge, to explore the PINK1 -/- rat’s capability to complete a food incentivized maze, during the premotor phase. In line with the findings of this study, prior cohorts of PINK1 -/- rats in our laboratory have consistently exhibited hyperkinetic behavior before the age of 6 months [8]. Notably, these outcomes contrast with reports from other studies, where the timing of initial motor deficits and the extent of dopamine (DA) loss in this model range widely, with some indicating no deficits and others observing deficits emerging between 4 to 8 months [7-9, 31].…”
supporting
confidence: 84%
“…The PINK1 -/rat, a genetic preclinical model of early-stage PD, may provide an opportunity to evaluate cognitive impairments that manifest during the premotor phase of PD. Still in its infancy, studies using the PINK1 -/model show some controversy about the age of onset of symptoms and the extent of these deficits across the lifespan of the rat model [7][8][9][10][11]. Apart from motor dysfunction, one lab has reported vocalization deficits in PINK1 -/rats [9], and only one study to-date has found object discrimination deficits at 5-months-old using the novel object recognition (NOR) task as a premotor feature in this model [11].…”
Section: Introductionmentioning
confidence: 99%
“…The GenElute™ Mammalian Genomic DNA Miniprep kit was used with minor changes to the procedure. The full methodological procedure has been previously published by our lab (Salvatore et al, 2022)…”
Section: Methodsmentioning
confidence: 99%
“…However, only one study has addressed whether aging may be a relevant factor in the inconsistent timing of motor phenotype onset against impaired DA signaling (Zhi et al, 2019). Thus far, only moderate loss, if any, of nigrostriatal neurons, DA, or tyrosine hydroxylase (TH) has ever been reported in this model (Dave et al, 2014;Villeneuve et al, 2016), and any DA loss is nowhere near the severity seen in human PD at diagnosis (Villeneuve et al, 2017;Dave et al, 2014;Creed et al, 2019Creed et al, , 2020Zhi et al, 2019;Salvatore et al, 2022). Moreover, striatal DA or TH loss has not correlated with motor impairments (Dave et al, 2014;de Haas et al, 2019;Marquis et al, 2020).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation